Hubungan Antara Tingkat Pendidikan Formal Dan Pengetahuan Orang Tua Tentang Ispa Pada Balita Di Puskesmas Gatak - Ristiyanto, Rudi; , dr. N. Juni Triastuti, M. Med. Ed; , dr. Sri Wahyu Basuki, M.Kes (2015)
Background : ISPA is a respiratory infection caused by microorganisms 2 viral and bacterial agents. Viral agents 90% cause of acute respiratory tract infections. Objective : The study aims to determine the relationship between levels of formal education and knowledge of parents of ISPA in children under five in Health Gatak. Methods: The study was observational analytic research with cross sectional approach implemented in Clinic Gatak, Sukoharjo in January 2015. The study population is the elderly patients aged ≤ 5 years ISPA having children ≤5 years of age ISPA patients in Clinic Gatak, Sukoharjo. Retrieval technique using a convenience sampling with a sample of 72 people. The technique of collecting data using questionnaires given to respondents directly. Analysis and presentation of data using chi-square analysis with software statically Product and Service Solutions (SPSS) 17.0 for Windows. Results : The results of the research that respondent old toddler majority of respondents are aged 31-40 years, had high school/equivalent, and have resided for 1-5 years. Respondents were mostly children under five respondents aged 25- 36 months and the female. The level of parental knowledge about ARI largely parental knowledge about ARI in either category. Conclusion : There is a relationship between the level of formal education and knowledge of parents of ARI in children under five in the health center level Gatak the relationship is strong enough, the p-value <0.05.